Opening the Density Functional Theory Black Box: A Collection of Pedagogic Jupyter Notebooks - Hirschi, Jacob S.; Bashirova, Dayana; Zuehlsdorff, Tim J. (Journal of chemical education, 2023)
Density functional theory (DFT) is indubitably the most popular and among the most successful approaches for approximately solving the many-electron Schrödinger equation. The level of understanding on the part of both researchers and students using DFT, however, is lacking, given the availability of black-box software. The present work addresses this knowledge gap by providing three Jupyter notebooks, easily accessible through the Google Colaboratory (GitHub repository: https://github.com/tjz21/DFT_PIB_Code), that provide a short skirmish with the fundamentals of DFT through a particle in a box-type model system. These notebooks were tested in conjunction with a problem worksheet in a graduate-level quantum chemistry course; pre- and postactivity survey results reveal largely positive reactions to this implementation and sustained enthusiasm for the subject.